Tooth loss and alveolar bone crest loss during supportive periodontal therapy in patients with generalized aggressive periodontitis: retrospective study with follow‐up of 8 to 15 years. (7th October 2016) - Díaz‐Faes, Lucía; Guerrero, Adrián; Magán‐Fernández, Antonio; Bravo, Manuel; Mesa, Francisco
Abstract: Aim: To determine the incidence of tooth loss in patients with generalized aggressive periodontitis (GAgP) during supportive periodontal therapy (SPT), identify tooth loss risk factors, and quantify alveolar crest height changes on periapical X‐ray during follow‐up. Material and Methods: This retrospective study included 25 GAgP patients with 656 teeth after periodontal treatment (baseline). Data were gathered on sociodemographic, periodontal, and radiological variables at baseline and at the end of follow‐up. Linear regression models were used to assess the association of risk factors with tooth loss. Results: Twenty‐eight teeth were extracted during SPT. The mean tooth loss per patient was 1.12 ± 2.01 for all causes and 0.9 ± 2.0 for periodontal disease after a mean follow‐up of 10.9 ± 2 years. Clinical variables were improved at the end of follow‐up, with a mean reduction of −1 ± 0.8 mm in probing pocket depth (−0.7 to −1.3, 95% CI) and −0.6 ± 0.9 mm in clinical attachment loss (−0.9 to −0.2, 95% CI). Mean alveolar bone crest loss at the end of follow‐up was 0.36 ± 0.56 mm (0.10–0.61, 95% CI). Smoking was associated with tooth loss ( p = 0.052). Conclusions: Tooth loss rate was low in GAgP in a regular supportive care programme. Clinical variables improved, and bone loss was minimal over time. Smoking was associated with tooth loss.